2013
DOI: 10.1016/j.ccr.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Independence 1 Antagonizes a p53-Induced DNA Damage Response Pathway in Lymphoblastic Leukemia

Abstract: Summary Most patients with acute lymphoblastic leukemia (ALL) fail current treatments highlighting the need for better therapies. Since oncogenic signaling activates a p53-dependent DNA-damage response and apoptosis, leukemic cells must devise appropriate countermeasures. We show here that growth factor independence 1 (Gfi1) can serve such a function, since Gfi1 ablation exacerbates p53 responses, and lowers the threshold for p53-induced cell death. Specifically, Gfi1 restricts p53 activity and expression of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 49 publications
8
84
1
Order By: Relevance
“…Staining of apoptotic cells and apoptotic bodies was similar when comparing PTTG-Tg mice (n ϭ 4) withWT mice (n ϭ 4) (1.05-fold change, P value not significant) ( Figure 5D, i and ii). The presence of apoptosis was also determined through measurement of mRNA levels of the proapoptotic genes bax and Bbc3 (Puma) (57,58). Results were similar when comparing hPTTG-Tg and WT mice (0.99-and 0.95-fold change, respectively, n ϭ 10, P value not significant) (Figure 5Diii).…”
Section: Hpttg Regulates Egf Expression and Secretion In Vivomentioning
confidence: 52%
“…Staining of apoptotic cells and apoptotic bodies was similar when comparing PTTG-Tg mice (n ϭ 4) withWT mice (n ϭ 4) (1.05-fold change, P value not significant) ( Figure 5D, i and ii). The presence of apoptosis was also determined through measurement of mRNA levels of the proapoptotic genes bax and Bbc3 (Puma) (57,58). Results were similar when comparing hPTTG-Tg and WT mice (0.99-and 0.95-fold change, respectively, n ϭ 10, P value not significant) (Figure 5Diii).…”
Section: Hpttg Regulates Egf Expression and Secretion In Vivomentioning
confidence: 52%
“…[52][53][54] Similar analyses with murine Gfi1b-deficient HSCs, megakaryocytes, or erythroid cells demonstrated that Gfi1b helps to establish gene expression programs necessary for the development of both erythroid and megakaryocytic lineages 29,32,55 and confirms the complementary roles of Gfi1 and Gfi1b in hematopoiesis already suspected by their differential, cell type-specific expression pattern.…”
Section: 3944-48mentioning
confidence: 71%
“…72 Experiments with conditionally deficient mice have shown that Gfi1 is required for efficient T-cell tumorigenesis, regardless of whether malignant transformation was initiated retrovirally, by chemical carcinogenesis, or by Notch1 activation. 52 This effect could also be shown for human cells because inhibition of GFI1 in primary human T-ALL inhibited their expansion in immune-deficient mice. More specifically, this study provided evidence that Gfi1 is an "oncorequisite" factor required for T-cell lymphomagenesis by limiting the ability of p53 to induce apoptosis during malignant transformation; that is, loss of Gfi1 led to reactivation of p53 in T-cell tumor cells and induced cell death.…”
Section: Lymphoma and Leukemia T-cell Lymphoma And Acute T-cell Lymphmentioning
confidence: 94%
See 1 more Smart Citation
“…Together, GFI1/1B are activated in at least one-third of G3-MBs (80). In mouse models of acute lymphoblastic leukemia, Gfi1 restricts p53 activity by repressing its proapoptotic targets (81,82). In hematopoietic cells, Gfi1/1b recruit the corepressor CoREST, the histone demethylase LSD1, and histone deacetylases (HDACs) 1 and 2 to target promoters involved in lineage differentiation (83).…”
Section: Groupmentioning
confidence: 99%